Cytotoxic and mutagenic in vitro assessment of two organosulfur compounds derived from onion to be used in the food industry. (1st January 2015) - Llana-Ruiz-Cabello, María; Maisanaba, Sara; Gutiérrez-Praena, Daniel; Prieto, Ana I.; Pichardo, Silvia; Jos, Ángeles; Moreno, F. Javier; Cameán, Ana María
Highlights: Dipropyl disulphide and dipropyl sulphide had no toxic effects on Caco-2 cells. Two organosulfur compounds from onion seems safe to be used in the food industry. Dipropyl disulphide and dipropyl sulphide did not induce mutagenicity in the Ames Test. Abstract: Edible members of the Allium family are widely used since they exhibit antioxidant and antibacterial related to the organosulphur compounds. One the most promising use of Allium species, hence, onion essential oil, could be in the packaging food industry. The present work aims to assess the safety of two organosulphur compounds present in onion essential oil; dipropyl disulphide, dipropyl sulphide and their mixture. For this purpose, cytotoxicity, reactive oxygen species and glutathione contents, and ultrastructural cellular damages were studied in the human intestinal cells, Caco-2, exposed to these organosulphur compounds. Moreover, their potential mutagenicity was also assessed. The results revealed no significant adverse effects. Additionally, reactive oxygen species scavenger activity was observed for both compounds. Therefore, they could be a good natural alternative to other synthetic antioxidant and antibacterial substances used in the food industry.